The PENGUJIAN PRODUKSI BEBERAPA JAGUNG (ZEA MAYS L.) HIBRIDA UNTUK VARIETAS PAKAN BIJI DAN PAKAN SILASE - Heri Kustanto; Hilmi Arija Fachrian; Lutfi Aris Sasongko; Renan Subantoro; Dewi Hastuti (Mediagro: Jurnal Ilmu-ilmu Pertanian, 2025)
Maize is the second most important food commodity after rice and a the main source of carbohydrate in Indonesia. The aim of this study was to determine the potential production potential and the appearance of several plant characters in several corn hybrids. The research method was conducted using Randomized Completed Design (RCD)with 3 replications. Analysis of data was done by analysis of variance and if there was a real effect, it was continued with the Honest Significant Difference (HSD). The results showed variation in phenotype appearance on each hybrid tested especially on the characters: leaf length, cob length, cob diameter and water content, weight character per cob, cob weight per plot and yield per hectare. The tested hybrids showed high yielding ability and were quite competitive when compared to current commercial varieties. compared to commercial varieties currently in the market.So it can be said that UWH 1, UWH 2, UWH 3, UWH 5 and UWH 6 can be developed into new hybrid varieties. be developed into new competitive hybrid varieties both for the purposes of corn feed grain and fresh feed forage (Silage).